The most beautiful girl in Cuba - Cleeton, Chanel (Berkley, 2021)
"At the end of the nineteenth century, three revolutionary women fight for freedom in New York Times bestselling author Chanel Cleeton's captivating new novel inspired by real-life events and the true story of a legendary Cuban woman-Evangelina Cisneros-who changed the course of history. A feud rages in Gilded Age New York City between newspaper tycoons William Randolph Hearst and Joseph Pulitzer. When Grace Harrington lands a job at Hearst's newspaper in 1896, she's caught in a cutthroat world where one scoop can make or break your career, but it's a story emerging from Cuba that changes her life. Unjustly imprisoned in a notorious Havana women's jail, eighteen-year-old Evangelina Cisneros dreams of a Cuba free from Spanish oppression. When Hearst learns of her plight and splashes her image on the front page of his paper, proclaiming her, "The Most Beautiful Girl in Cuba," she becomes a rallying cry for American intervention in the battle for Cuban independence. With the help of Marina Perez, a courier secretly working for the Cuban revolutionaries in Havana, Grace and Hearst's staff attempt to free Evangelina. But when Cuban civilians are forced into reconcentration camps and the explosion of the USS Maine propels the United States and Spain toward war, the three women must risk everything in their fight for freedom"--